Three Distinct Phases of Isoprene Formation during Growth and Sporulation of Bacillus subtilis - Wagner, William P. (American Society for Microbiology, 1999)
During growth on a glucose-tryptone medium, Bacillus subtilis 6051 (Marburg strain) exhibited three phases of isoprene (2-methyl-1,3-butadiene) formation, corresponding to (i) glucose catabolism and secretion of acetoin, (ii) catabolism of acetoin, and (iii) the early stages of sporulation. These results establish an experimental system for studying the biological role of isoprene formation.